Pengembangan Sistem Informasi Manajemen Penjadwalan Akademi Basket Berbasis Web Menggunakan Rapid Application Development - Vannes Yanuarta Salim; Soetam Rizky Wicaksono (JURNAL TEKNOSAINS KODEPENA, 2026)
This study aims to develop a web-based basketball academy scheduling management information system that integrates student registration, training scheduling, tuition payment, attendance, performance assessment, and coach payroll into a single platform. Prior to this study, Greyhound Basketball Academy managed its operational activities using separate media, resulting in delays in information delivery, data redundancy, and coordination challenges. The system was developed using the Rapid Application Development (RAD) methodology, consisting of the Requirement Planning, User Design, Construction, and Cutover phases. The implementation results demonstrate that the system successfully integrates the academy's operational processes through a centralized scheduling mechanism, while Black-Box Testing confirms that all major system functions operate according to the specified functional requirements. Therefore, the developed system effectively supports integrated operational management and maintains data consistency across interconnected business processes.